From golden age to golden age: Australia's great leap forward? - Paul Frijters; Robert George Gregory (Institute for the Study of Labor (IZA), 2006)
The twenty-five years after WW 2 witnessed strong labour market institutions and beneficial labour market outcomes - high wage growth and integration of low-skilled immigrants. Then came the macro shocks of the mid 1970s. Labour market outcomes deteriorated as full-time employment population ratios fell, particularly among males; unemployment and welfare use increased; and real wages grew slowly. The golden age passed. In response, successive governments have increasingly begun to dismantle the institutional framework. We address this transition within a simple long run graphical framework to help us marshal facts and arguments and to discuss the likely impact of institutional reform.
Keywords: J0; D6; E6; L5; O3; 330; unemployment; wage growth; welfare use; institutional reform; Australia; Wirtschaftsreform; Sozialreform; Australien